2021
DOI: 10.1007/s00394-021-02583-3
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgal protein hydrolysates from Palmaria palmata influence the ‘incretin effect’ in vitro via DPP-4 inhibition and upregulation of insulin, GLP-1 and GIP secretion

Abstract: Purpose This study investigated metabolic benefits of protein hydrolysates from the macroalgae Palmaria palmata, previously shown to inhibit dipeptidylpeptidase-4 (DPP-4) activity in vitro. Methods Previously, Alcalase/Flavourzyme-produced P. palmata protein hydrolysate (PPPH) improved glycaemia and insulin production in streptozotocin-induced diabetic mice. Here the PPPH, was compared to alternative Alcalase, bromelain and Promod-derived hydrolysates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…An increase in calcium transmembrane mobilization, as well as an upregulation of cyclic adenosine monophosphate (cAMP) was found liable for the overall incretin effect. When testing these effects in vivo with mice (100 mg/kg body weight), it was found an improved glucose tolerance, as well as satiety response after 90 min of oral administration, which would indicate a positive increase in GLP-1 and other incretin upregulation [ 129 ].…”
Section: Bioactive Properties and Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in calcium transmembrane mobilization, as well as an upregulation of cyclic adenosine monophosphate (cAMP) was found liable for the overall incretin effect. When testing these effects in vivo with mice (100 mg/kg body weight), it was found an improved glucose tolerance, as well as satiety response after 90 min of oral administration, which would indicate a positive increase in GLP-1 and other incretin upregulation [ 129 ].…”
Section: Bioactive Properties and Mechanisms Of Actionmentioning
confidence: 99%
“…Seaweed BAPs may also act as α-glucosidase inhibitors, reducing gut glucose absorption and subsequent glycemic levels [ 54 ]. Given that these effects have been described in animal models, there is a great potential for these peptides as dietary supplements for diabetes and/or obesity management [ 128 , 129 ]. The anti-inflammatory or antitumoral properties of seaweed BAPs have also been highlighted.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Alcalase, bromelain, and Promod-derived hydrolysates dipeptidyl peptidase IV (DPP-IV) inhibitory activities, [111] Alcalase/Flavourzyme hydrolysates Antihyperglycemic/antidiabetic potential [112] Peptides: ILAP, LLAP, MAGVDHI DPP-IV inhibitory activities [113] Papain hydrolysates: NIGK Platelet-activating factor acetyl-hydrolase (PAF-AH) inhibitory peptides [114] IRLIIVLMPILMA…”
Section: Functional Properties Of Seaweed Proteins and Their Role In ...mentioning
confidence: 99%
“…demonstrated activity against Seaweeds can be a natural source of DPP-IV inhibitors. Studies have reported that protein hydrolysates of P. palmata have DPP-IV inhibitory activities that are useful for the management of T2DM [111,144] and obesity [111]. Oral administration of P. palmata protein hydrolysate derived from Alcalase and Flavourzyme reduced food intake by streptozotocininduced diabetic mice and showed antihyperglycemic effects [112].…”
Section: Peptidesmentioning
confidence: 99%
“…For example, P. palmata, was used to obtain a protein hydrolysate with the ability of improving glycemia and insulin production when assessed in vivo, as the specific Alcalase/Flavourzyme protein hydrolysate enhanced the glucose tolerance and satiety. Thus, these P. palmata protein hydrolysates were suggested as potential molecules for managing two chronic diseases with a worldwide increasing prevalence: obesity and type-2 diabetes mellitus [19]. Another work based on proteins extracted from the same species proved their antiproliferative capacity against five human cancer cell lines derived from breast (MCF-7), liver (HepG-2), gastric (SGC-7901), lung (A549), and colon cancers (HT-29), with half inhibitory concentrations (IC 50 ) ranging between 192 and 317 µg/mL [20].…”
Section: Rhodophytamentioning
confidence: 99%